Genotype-phenotype dilemma in a case of sudden cardiac death with the E1053K mutation and a deletion in the SCN5A gene - Jenewein, Tina; Wolpert, Christian (Forensic science international, 2017)
Mutations in the cardiac sodium channel gene SCN5A may result in various arrhythmia syndromes such as long QT syndrome type 3 (LQTS), Brugada syndrome (BrS), sick sinus syndrome (SSS), cardiac conduction diseases (CCD) and possibly dilated cardiomyopathy (DCM). In most of these inherited cardiac arrhythmia syndromes the phenotypical expression may range from asymptomatic phenotypes to sudden cardiac death (SCD). A 16-year-old female died during sleep. Autopsy did not reveal any explanation for her death and a genetic analysis was performed. A variant in the SCN5A gene (E1053K) that was previously described as disease causing was detected. Family members are carriers of the same E1053K variant, some even in a homozygous state, but surprisingly did not exhibit any pathological cardiac phenotype. Due to the lack of genotype-phenotype correlation further genetic studies were performed. A novel deletion in the promoter region of SCN5A was identified in the sudden death victim but was absent in other family members. These findings demonstrate the difficulties in interpreting the results of a family-based genetic screening and underline the phenotypic variability of SCN5A mutations.